Utilizing YouTube’s Authentic Materials for Teaching Japanese as a Foreign Language to Young Learners - Khasanah, Ismatul; Utomo, Kireina Fernanda (Universitas Negeri Semarang, 2024)
This paper aims to investigate on the guided use of YouTube inside the classroom in the context of elementary education in Malang, Indonesia. As a versatile medium for providing authentic materials to learn a foreign language, YouTube has been widely utilized as an affordable alternative to facilitate authentic teaching and learning activities. Teachers can find abundant materials to use inside the classroom on YouTube, and learners can easily access the same material when they are home under their parents’ surveillance. In this study, YouTube provides authentic audio-visual entertainment where young learners are exposed to Japanese songs to memorize the vocabulary. This study used a descriptive qualitative method where the collected data are primary—from young learners by observing them learning Japanese in an extracurricular program—and secondary—taken from several literature reviews related to the current study. Learning Japanese using YouTube videos shows positive results with the support of students who can understand the material. Apart from that, students also said that learning using video methods was more fun and not dull. In this way, YouTube videos can facilitate the learning process of students learning basic Japanese at the elementary school or early childhood level.